Marketing Strategy of Live Seafood Restaurants: Empowering Women to Achieve SDGs - Ramli, Ramli; Jasila, Ismi; Rasidi, Moh. (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
The culinary business in Situbondo Regency offers an opportunity to contribute to economic growth and sustainability, aligning with the United Nations Sustainable Development Goals (SDGs). Inspired by this potential, a housewife named Diah Palupi pioneered a unique seafood restaurant concept: a live seafood restaurant. Despite initial success, the business recently experienced a sales decline, necessitating an effective marketing strategy to ensure its sustainability and relevance to SDG targets. This study aims to formulate the right marketing strategy for the Live Seafood Restaurant in Situbondo Regency. The analysis methods used to formulate the strategy are SWOT and QSPM analysis. The results recommend that the Live Seafood Restaurant business implement a diversification strategy. Meanwhile, the priority strategies are 1) Designing a diverse seafood menu and distinctive taste with good quality and competitive prices to win the competition, 2) Conducting intensive promotions and collaborating with stakeholders to expand networks and ease of access, 3) Designing a seafood restaurant based on tourist destinations and market needs, 4) Developing fish farming based on technology to ensure the availability of continuous raw materials at competitive prices and good quality and 5) Conducting a feasibility study again on the current position of the live seafood restaurant business. By addressing these strategies, the live seafood restaurant not only aims to revitalize its business performance but also contributes to broader sustainable development objectives, enhancing its impact on local communities and environmental stewardship.